Malawi : 2018 Article IV Consultation and Request for a Three-Year Arrangement Under the Extended Credit Facility. (IMF Staff Country Reports; Country Report, 2018)
This 2018 Article IV Consultation highlights that the economy of Malawi recently rebounded from two years of drought. Growth picked up from 2.3 percent in 2016 to an estimated 4.0 percent in 2017 owing to a recovery in agricultural production. Inflation has been reduced below 10 percent owing to the stabilization of food prices, prudent fiscal and monetary policies, and a stable exchange rate. Economic growth is expected to increase gradually, reaching over 6 percent in the medium term. Growth will be supported by enhanced infrastructure investment and social services as well as an improved business environment, which will boost confidence and unlock the economy's potential for higher, more broad-based, and resilient growth and employment.